A novel system of MnO2-mullite-cordierite composite particle with NaClO for Methylene blue decolorization. (1st May 2018) - Zhi, Suli; Tian, Liang; Li, Nan; Zhang, Keqiang
Abstract: The MnO2 -mullite-cordierite composite particle (MnO2 -MCP) was prepared and firstly was applied as catalyst with sodium hypochlorite (NaOCl) as oxidant in heterogeneous Fenton-like system for methylene blue (MB) decolorization. The MnO2 -MCP was characterized by XRD, SEM, EDS and BET analysis. The decolorization efficiencies of MB/MnO2 -MCP, MB/NaClO, (MB after filtrating MnO2 -MCP)/NaClO and MB/MnO2 -MCP/NaClO were compared, which confirmed the interaction ability between MnO2 -MCP and NaClO. After evaluating the role of adsorption of MB by MnO2 -MCP, the catalytic oxidation effects of MnO2 -MCP with NaClO on MB were exploited. The adsorption results showed that the new porous catalyst had certain adsorption capacity for MB and the adsorption fit best with Langmuir model. The central composite rotatable design (CCD) of response surface methodology (RSM) was used to design catalytic oxidation experiments of MB/MnO2 -MCP/NaClO system, with influencing factors of catalyst dose, NaClO concentration, pH and initial MB concentration. The optimum conditions were 5.97 mM of NaClO, 37.9 g/L of catalyst dose, 5.74 of pH value and 100.71 mg/L of initial MB concentration, which could ensure nearly 100% MB decolorization. The effect of radical scavengers elucidated that superoxide anion (O2 − ) was the main species to decolorize MB. Then the possible degradation mechanism and pathway of MB were proposed in this MnO2 -MCP/NaClO system. Graphical abstract: Image 1 Highlights: Commercial NaClO was firstly used as the heterogeneous Fenton-like oxidant. MnO2 -mullite-cordierite composite was exploited as catalyst to purify wastewater. NaClO/MnO2 -MCP guarantees high decolorization efficiency in a wide pH range. NaClO/MnO2 -MCP can adjust the pH of acidic wastewater when treating wastewater. Catalytic mechanism and degrading pathway of MB were proposed.